Tożsamość kultury prawnej a legitymizacja prawa - Bekrycht, Tomasz (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
The paper analyses some elements which create the identity of legal culture. These elements are determined by Greek philosophy, Roman law (the Mediterranean culture) and Christian solidarity. These included positive law (legem ponere), jurisprudence, academic teaching, legal text, axiological autonomy of law, Roman law as origin of civil law and its reception, legitimization of law. The paper focuses particularly on problematic aspects of legitimization of law. In the literature of jurisprudence the problem of the legitimacy (justifying) of law is presented as the justification for the external validity of law or as a justification for the absolute validity. The history of philosophy of law demonstrates that we can talk about same arguments, which may be referred to as transcendental. Those are ultimate conditions of justifying any kind of being – here this particular being is the law. Firstly, this paper presents two trends (traditions) in the literature of philosophy that have developed the concept of transcendental method, and thus the content of the concept of transcendentalism. Secondly, it presents four arguments which justify the existence of law and which can be called the transcendental arguments.